2018
DOI: 10.1177/2043808718798076
|View full text |Cite
|
Sign up to set email alerts
|

Attentional control associated with core cognitive maintenance factors of social anxiety

Abstract: Models of social anxiety emphasize anticipatory processing (AP) and post-event processing (PEP) as repetitive negative thinking (RNT) processes that occur before and after social-evaluative events, respectively. Both AP and PEP have been implicated as maladaptive processes which maintain social anxiety. Accordingly, a common vulnerability, such as poor attentional control, may serve to maintain both. The present research included two separate samples to investigate the relationship between attentional control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…The present findings are in line with the metacognitive model of psychological disorders [5, 14] and with previous studies that have confirmed a role for metacognitive beliefs [19, 20] and attentional control [2931] in psychopathology. Moreover, previous studies have found support for an association between greater maladaptive metacognitive beliefs and lower attentional control, and that these constructs can explain individual variance in several types of psychopathology [32–35, 47].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present findings are in line with the metacognitive model of psychological disorders [5, 14] and with previous studies that have confirmed a role for metacognitive beliefs [19, 20] and attentional control [2931] in psychopathology. Moreover, previous studies have found support for an association between greater maladaptive metacognitive beliefs and lower attentional control, and that these constructs can explain individual variance in several types of psychopathology [32–35, 47].…”
Section: Discussionsupporting
confidence: 93%
“…We therefore assume that the ACS offers a measure of metacognitive beliefs about attention even though there is some overlap between the ACS and behavioural assessment of attention control abilities (e.g., [28]). ACS scores have been identified as negatively related to depression [29], generalized anxiety [30], and social anxiety [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, subscales of effortful control may differ in their relationship to anxiety and its development. Attentional control deficits are implicated in social anxiety (Moriya & Tanno, 2008; Morrison & Heimberg, 2013; Sluis et al, 2018) and greater attentional and activation control abilities are related to lower shyness in children aged 3–7 years (Eggum-Wilkens et al, 2016). When looking at subscales, Eggum-Wilkens et al reported that inhibitory control was associated with consistently higher, albeit fastest reducing, overall levels of shyness compared with activation and attentional control.…”
Section: The Present Studiesmentioning
confidence: 99%